STRATEGI PEMBELAJARAN DI ANTARA GURU TERHADAP SISWA DALAM KONTEKS MEMECAHKAN KESULITAN BELAJAR - Pudun Tadam (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract: Strategic Learning involves Learning Strategies and Teaching Strategies that can help bring success to a student. The research objective answers the question: What is the meaning of a Learning Strategy? What is an Effective Learning Strategy? What are the Learning Strategies among Teachers against Students in the Context of Solving Learning Difficulties? The answer is: Learning strategies are the methods that will be selected and used by a teacher to deliver learning material that aims to make it easier for students to receive and understand learning material, which in the end can be mastered learning objectives at the end of learning activities. Three aspects of effective learning strategies are: (1) Students Need Continuous Strategic Instruction. (2) Teachers Promote Self-Awareness in Metacognition in the Classroom. (3) Teachers Can Recognize and Understand Different Learning Profiles. Learning Strategies between Teachers and Students in the Context of Solving Learning Difficulties are: (1) learning difficulties manifested in classrooms, (2) difficulties demonstrated by students in classrooms, and (3) strategies to help students who have difficulty paying attention in class . Abstrak: Strategic Learning melibatkan Strategi Pembelajaran dan Strategi Pengajaran yang dapat membantu membawa kejayaan kepada seorang mahasiswa. Tujuan penelitian menjawab pertanyaan: Apakah pengertian Strategi Pembelajaran? Bagaimanakah Strategi Pembelajaran yang Efektif? Bagaimanakah Strategi Pembelajaran di antara Guru terhadap Siswa dalam Konteks Memecahkan Kesulitan Belajar? Jawabannya adalah: Strategi pembelajaran adalah cara-cara yang akan dipilih dan digunakan oleh seorang pengajar untuk menyampaikan materi pembelajaran yang bertujuan untuk memudahkan peserta didik menerima dan memahami materi pembelajaran, yang pada akhirnya tujuan pembelajaran dapat dikuasainya di akhir kegiatan belajar. Tiga hal strategi pembelajaran yang efektif adalah: (1) Siswa  Memerlukan Instruksi Strategi yang Berkelanjutan. (2) Guru  Mempromosikan Kesadaran Diri dalam Metakognisi di Kelas. (3) Guru-guru Dapat Mengenali dan Memahami Profil Pembelajaran yang Berbeda. Strategi Pembelajaran di antara Guru terhadap Siswa dalam Konteks Memecahkan Kesulitan Belajar adalah: (1) kesulitan belajar dimanifestasi dalam bilik kelas, (2) kesulitan didemonstrasi oleh siswa dalam bilik kelas, dan (3) strategi-strategi untuk membantu siswa yang kesulitan perhatian di kelas.